Adaptation of a Fungal Pathogen to Host Quantitative Resistance - Frézal, Lise; Jacqua, Guy; Neema, Claire (Frontiers in Plant Science, 2018)
Impact of host quantitative resistance on pathogen evolution is still poorly documented. In our study, we characterized the adaptation of the pathogenic fungus Colletotrichum gloeosporioides, to the quantitative resistance of its host, the water yam (Dioscorea alata). Genetic and pathogenic diversities of C. gloeosporioides populations were specified at the field scale. We used nuclear markers to describe fungal population structuring within and between six fields of three cultivars differently susceptible to the fungus. Strain aggressiveness was then quantified in the laboratory through cross-inoculation tests. The high level of genetic diversity and significant linkage disequilibrium revealed a significant influence of clonal reproduction in the C. gloeosporioides evolution. The recorded fungal migration between fields was weak (evidence for a dispersion mode via tubers rather than splashing dispersal), which provides the first molecular evidence for limited C. gloeosporioides migration via yam tuber exchanges. Colletotrichum gloeosporioides’s populations are adapted to their host resistance. The aggressiveness of the fungal clones seems to have evolved towards an accumulation of components specific to each host cultivar. Despite the remaining marks of adaptation to the former widely cultivated host, adaptation to current cultivars was clearly depicted.